EVALUASI KEGIATAN AKUAKULTUR DI KOLONG PASCA TAMBANG : ANALISIS PENCEMARAN AIR KOLONG - Eva Prasetiyono (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2015)
Ex-tin mining lakes are commonly used by many people in Bangka Island for fish farming activities. The water logs of post mining lakes have been used for fish farming activities. We hypothesized possibly environmental pollution related to the water quality. This paper aimed to evaluate fish farming activities by the local communities using the waterlogs of post mining lakes. The evaluation was based on heavy metals extent in the water using survey method with purposive sampling in order to determine which extin mining lakes would be feasible for aquaculture activities. The data of the content of heavy metals and water qualities were analyzed using the method of Pollution Index (PI). According to the age of mining lakes, the five ex-tin mining lakes which has been observed. The results showed one new aged, two middle aged, and one old age; meets the quality standard eligibility for fish farming activities, while the middle aged was low polluted. The age of ex-tin mining lakes not affected nor the extent of the pollution levels or water qualities.Keywords : ex-tin mining, lakes, aquaculture, water qualities, pollution index, fish